2008
DOI: 10.1128/jb.00217-08
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors CysB and SfnR Constitute the Hierarchical Regulatory System for the Sulfate Starvation Response inPseudomonas putida

Abstract: Pseudomonas putida DS1 is able to utilize dimethyl sulfone as a sulfur source. Expression of the sfnFG operon responsible for dimethyl sulfone oxygenation is directly regulated by a 54 -dependent transcriptional activator, SfnR, which is encoded within the sfnECR operon. We investigated the transcription mechanism for the sulfate starvation-induced expression of these sfn operons. Using an in vivo transcription assay and in vitro DNAbinding experiments, we revealed that SfnR negatively regulates the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…However, because CysB appeared to bind to the pqsR-P4 fragment with low affinity, it is unclear whether this interaction is relevant in vivo or is simply due to nonspecific interactions between CysB and DNA sequences close to the pqsR transcriptional start sites. Aside from a preference for A-T-rich DNA sequences, CysB binding sites lack a strong consensus sequence (59,61), and we were unable to clearly identify specific sequences in the pqsR or cysH promoter that might be recognized by CysB. Nevertheless, these data provide evidence that both cysH and pqsR are directly regulated by CysB in P. aeruginosa.…”
Section: Fig 5 Overexpression Of Cysb Represses Pqsr Expression and Imentioning
confidence: 42%
See 2 more Smart Citations
“…However, because CysB appeared to bind to the pqsR-P4 fragment with low affinity, it is unclear whether this interaction is relevant in vivo or is simply due to nonspecific interactions between CysB and DNA sequences close to the pqsR transcriptional start sites. Aside from a preference for A-T-rich DNA sequences, CysB binding sites lack a strong consensus sequence (59,61), and we were unable to clearly identify specific sequences in the pqsR or cysH promoter that might be recognized by CysB. Nevertheless, these data provide evidence that both cysH and pqsR are directly regulated by CysB in P. aeruginosa.…”
Section: Fig 5 Overexpression Of Cysb Represses Pqsr Expression and Imentioning
confidence: 42%
“…6). Furthermore, previous studies showed that the in vitro DNA binding activity of recombinant CysB proteins from P. aeruginosa and P. putida was not affected by NAS or OAS (44,59). So while CysB seems to fulfill the same regulatory functions in P. aeruginosa, it appears to respond to different signals than those in enteric bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the inducer N-acetylserine inhibits binding of CysB to the cysB promoter and partially reverses inhibition of transcription initiation caused by CysB; this means that CysB has the ability to respond to acetylserine with either an increase or a decrease in affinity for different DNA sequences (Ostrowski and Kredich 1991). In contrast, in B. cenocepacia and Pseudomonas putida the function of CysB appears to be independent of the presence of O-acetylserine, indicating that CysB action may vary with respect to the recognition of an inducer (IwanickaNowicka et al 2007;Kouzuma et al 2008).…”
Section: Regulation Of the Cysptwa Operonmentioning
confidence: 94%
“…The data indicate that the mechanism by which the CmaR protein exerts its regulatory effect is via the control of the expression of the cmaR gene, rather than by modulating the activity of CmaR through effectors, as is the case for CysR. In Burkholderia cenocepacia and P. putida, the binding of the activator to the cys genes does not require effector molecules (Iwanicka-Nowicka et al, 2007;Kouzuma et al, 2008).…”
Section: Dna-binding Activity Of Cmarmentioning
confidence: 99%